2014
DOI: 10.1021/nn503732m
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-like Nanoparticles: Mimicking Shape, Flexibility, and Surface Biology of Platelets To Target Vascular Injuries

Abstract: Targeted delivery of therapeutic and imaging agents in the vascular compartment represents a significant hurdle in using nanomedicine for treating hemorrhage, thrombosis, and atherosclerosis. While several types of nanoparticles have been developed to meet this goal, their utility is limited by poor circulation, limited margination, and minimal targeting. Platelets have an innate ability to marginate to the vascular wall and specifically interact with vascular injury sites. These platelet functions are mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
302
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 302 publications
(309 citation statements)
references
References 58 publications
7
302
0
Order By: Relevance
“…6). An excellent example of this is the development of artificial (polymeric) erythrocytes that possess a discoidal shape, mechanical flexibility, biochemically mediated aggregation and heteromultivalent presentation of ligands for platelet binding and wound targeting [86]. Such morphologically diverse NVs show high specific adhesion and limited non-specific interactions with excellent haemostatic capability over more rigid, spherical counterparts, due to their propensity to marginate to the vascular wall, which results in a substantial reduction of bleeding time in vivo.…”
Section: Impact Of Nanovector Morphology On Performance In Vitro and mentioning
confidence: 99%
“…6). An excellent example of this is the development of artificial (polymeric) erythrocytes that possess a discoidal shape, mechanical flexibility, biochemically mediated aggregation and heteromultivalent presentation of ligands for platelet binding and wound targeting [86]. Such morphologically diverse NVs show high specific adhesion and limited non-specific interactions with excellent haemostatic capability over more rigid, spherical counterparts, due to their propensity to marginate to the vascular wall, which results in a substantial reduction of bleeding time in vivo.…”
Section: Impact Of Nanovector Morphology On Performance In Vitro and mentioning
confidence: 99%
“…[36][37][38] Current research in the field of platelet-mimetic technologies utilizes a wide variety of strategies including both naturally derived platelet derivatives and synthetic platelet strategies. In subsequent sections, we review various strategies that encompass a large range of approaches to achieve various goals such as wound targeting, drug delivery, and immune system evasion through platelet membrane cloaking.…”
Section: Platelets In Coagulation and Hemostasismentioning
confidence: 99%
“…45 As an alternative approach, studies performed by Nguyen et al 24 demonstrated that the body's existing platelets can be differentially stimulated using the protease activated receptor agonists PAR-1-agonist and PAR-4-agonist to selectively secrete VEGF, to promote angiogenesis, or endostatin, an anti-angiogenic factor. While the conclusions they drew from this study need to be tested under more applicable physiological conditions, such as in the presence of microbial agents, this method may present a useful Figure 2 Synthesis and analysis of platelet-like nanoparticles developed by Anselmo et al 36 (a) schematic and (b) scanning electron microscope images of layer-bylayer synthesis of nanoparticles using alternating layers of bovine serum albumin and poly(allylamine hydrochloride) (PAH) and a degraded core to achieve deformable particles with platelet-like discoid morphology. …”
Section: Platelet-mimetic Strategies and Technologies Natural Platelementioning
confidence: 99%
See 1 more Smart Citation
“…The design of novel nanoparticles capable of delivering drugs to the diseased sites and organs is expected to improve the therapy of various disorders, for which the systemic therapies lack sufficient efficacy. Surface functionalization of such nanoparticles is proposed to extend their circulation time and to reduce the adverse reactions from the circulating immune cells [5]. In a recent study by Hu et al, biomimetic nanoparticles were developed by coating polymeric nanoparticles with the membranes of human platelets.…”
mentioning
confidence: 99%